Student representation on boards of trustees in Auckland secondary schools : a thesis presented in partial fulfilment of the requirements for the degree of Master of Educational Administration, Massey University, New Zealand - Kelly, Oriel (Massey University, 1993)
The topic of this thesis is the contribution and effectiveness of the student representatives on a small group of secondary school Boards of Trustees in a New Zealand city. The placing of a student on the governing body of New Zealand secondary schools was made law on October 1st 1989. This study, undertaken in 1991, the third year of participation, endeavoured to evaluate the working contribution of these representatives. Effectiveness was measured in relation to the expectations of the representatives themselves, their colleagues, and in the eyes of those they represent. The literature review established that participation by students in school decision-making is necessary and commendable but difficult to achieve successfully. The New Zealand structure is unique; yet it is of a similar non-proportional, consultative nature to that in other countries and it was suspected that this model would suffer from the same difficulties as those overseas. These difficulties might include role definition, difficulties in communication and consultation, inadequacy of training for their role and objections to the presence of students on the boards. A variety of methods was employed. The primary method used questionnaires administered to 16 newly appointed student representatives at schools in the Auckland area as a wide focus. Questions covered the areas of expectations, role, training, communication channels and limitations on student representatives' contribution to their boards. The narrow focus observed the student representatives in the public aspect of their role at four large Auckland schools. Opinions of the students' effectiveness and contribution were also sought from their fellow board members and the student body being represented at each school. This was done by questionnaire and attitude scale respectively. The two pronged investigation of wide and narrow focus sampling in the overall design provided the triangulation necessary to confirm the findings. Major Findings The study established that the role of the student representative is unclear to both themselves and those they represent. The role is also limited (illegally) by their fellow board members who place restrictions, "common sense" though they may be, on the contributions of the students, and often without the students themselves realising that their role has been restricted in this way. The student role tends to be more one of observer than participant. As suspected, effective representation by consultation is difficult to achieve. There was a strong feeling that the students should have a voice on the board but communication channels were difficult to establish and maintain and the student voice was seldom heard at board meetings. Few student representatives reported receiving any training for their role. This must, in turn, reduce the effectiveness of the student voice. Opposition to the presence of students on the boards was not obvious but methods were employed to restrict the participation of the students in sensitive areas - such as staff or student discipline - despite such restrictions being illegal and in contravention of democratic and participatory rights. The inclusion of a student representative on secondary school Boards of Trustee has proved popular with the student body. However the lack of training, and the covert opposition to such students severely limits their effectiveness. It is to be hoped that the recent law change, making their inclusion optional, will not see the complete demise of their contribution.
Keywords: New Zealand -- Auckland; School boards; School board members; Student participation in administration; High schools -- Administration